Character Building dalam Literatur Islam Kontemporer - Astuti, Dian Fauzi (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2019)
Character building is one of the efforts of the Indonesian people to restore noble values ​​that have been distorted. The formation of character (character building) in Islam is really an effort to give birth to a man of knowledge, character, civilized and noble as practiced by the Messenger of Allah. (Madrasah Nabawiyah) which can be used as a reference model for building character education. In contemporary Islamic literature, character building is an effort to develop all aspects of humanity in the physical, emotional, spiritual and intellectual dimensions to produce individuals who have the character of faith, responsibility, care, honesty, courage and become citizens who are well. The model of instilling character values ​​through teaching, habituation, modeling, motivating, and enforcing rules that are implemented consistently and continuously in daily life at home, school, and in the community will form superior individuals as khalifah fi al-Ardli.